YESUS DI GETSEMANI SEBAGAI UNGKAPAN CINTA AGAPE (REFLEKSI TEOLOGIS MATIUS 26:36-46 - Parhusip, Bintang; Situmorang, Kalaudius Willy R. (Pastoralia Jurnal Penelitian Dosen, 2023)
The focus of this paper is to explain agape love through the story of the passion of Jesus in Gethsemane. Matthew 26:36-46 tells of Jesus prayer in Gethsemane as a model for building agape love. The methodology used in this research is a literature study to explore the theological reflections on Matthew 26:36-46 and its relation to the love of Peter and Judas. The passion story of Jesus shows the journey of eros love to agape love. The scheme of the triple prayer in Gethsemane shows the transformation of Jesus love. At the last point, Jesus was able to let go of everything and surrender to the will of the Father. This is the real proof of agape love, namely total obedience and self-sacrifice. This agape love is what Jesus passed on to Peter and Judas. Both have free will to choose, Peter chose to die for faith in Christ while Judas chose to despair and commit suicide. Peter was able to achieve agape love while Judas was entangled in eros love. The story of Peter and Judas becomes the foundation for the faithful to live love more deeply. Human life is a journey of love, namely from eros love to agape love which is Jesus himself.